KORELASI KANDUNGAN FENOLIK DAN AKTIVITAS ANTIOKSIDAN DAUN JAMBU METE - Kusumowati, Ika Trisharyanti Dian; Melannisa, Rosita; Ratri, Kartikaning (Universitas Muhamadiyah Surakarta, 2011)
The ethanolic extract of Anacardium occidentale L. leaves contains phenolic compounds, ? avonoids, alkaloids, saponins, tannins, and steroids that could have antioxidant activity. The aim of this research was to determine the correlation between the antioxidant activity and the phenolic compounds of the ethanol extract of Anacardium occidentale L. leaf. The DPPH methode was used to determine the antioxidant activity. The total phenolic determined using Folin-Ciocalteu reagent. There was a positive correlation between antioxidant activity and total phenolic content in the ethanolic extract of cashew leaf with correlation coef? cient R2 = 0.5888.Keywords: Anacardium occidentale L., antioxidant, phenolic compounds